Long Distance From Microvessel to Cancer Cell Predicts Poor Prognosis in Non-Small Cell Lung Cancer Patients - Ding, Haiying; Sun, Jiao; Song, Yu; Xin, Wenxiu; Zhu, Junfeng; Zhong, Like; Chen, Yinbo; Zhang, Yiwen; Tong, Yinghui; Fang, Luo (Frontiers in Oncology, 2021)
Background: Blood supply, which is crucial for nutrition and drug delivery, was determined by microvessel density as well as the diffusion distance between vessels and cancer cells. Therefore, we evaluated the distance from microvessels to cancer cells (Dmvcc) and its role in the prognosis of non-small cell lung cancer (NSCLC) patients. Methods: Patients with primary NSCLC were retrospectively analyzed. The tumor samples were immunochemically stained with CD31 to visualize the microvessels. The Dmvcc was defined as the mean distance from each microvessel to its nearest cancer cell in the “hot-spot” of an individual patient. The patients were stratified into short- and long-distance groups using five strategies, including dichotomy by the median value, optimal cutoff, trichotomy, quartation and per-10 µm increase. The correlation between the Dmvcc and survival was evaluated by using univariate and multivariate analyses with various Dmvcc strategies. Results: In total, 100 patients were analyzed. The median value of Dmvcc was 13.1 μm (ranged, 1.6 to 269.7 μm; mean value, 24.4 ± 33.5 μm). The optimal cutoff value of Dmvcc for predicting survival outcome was 20 μm. Dmvcc was significantly related to overall survival (OS) with all the five categories (p=0.001-0.000004) and progression-free survival (PFS) categorized by optimal cutoff value (p=0.024), trichotomy (p=0.041) and per-10 µm increase (p=0.040) after adjusting for other factors. Patients with longer Dmvcc (≥ 20 μm) were observed to have poor survival outcomes (OS: HR=13.5, 95CI: 4.42-41.18, p=0.000005; PFS: 3.26, 95CI: 1.56-6.81, p=0.002). A high Dmvcc per-10 µm was associated with a significantly increased risk of progression and cancer-related death by 98% (p=0.0001) and 30% (p=0.044), respectively. Conclusion: The NSCLC tissues had varying distances from microvessels to cancer cells, and long distances were strongly associated with poor survival.